The Cheat to Lose Diet : Cheat Big With the Foods You Love, Lose Fat Faster than ever Before, and Enjoy Keeping it Off! - Marion, Joel (New York Crown Publishers, 2007)
You start a new diet with every intention of sticking to it, cutting out all of your favorite foods and eating exactly what the diet tells you to. At first, the numbers on the scale go down, but after a short while, you hit a plateau. Then, feeling frustrated, weak, and unsatisfied, you do what we all do when a diet simply isn't working: quit. But fitness expert Marion has discovered a startling truth: cheating on your diet can actually accelerate fat loss. Based on cutting-edge medical research, the Cheat to Lose Diet reveals the hormonal connection between strategic cheating and fat loss that will change the way you diet forever. Here, finally, is a diet that works with your body to help you lose fat faster than restrictive dieting ever could.--From publisher description.
Include Index
Keywords: Weight loss -- Weight loss--Psychological aspects